Keterampilan Berpikir Kritis Siswa SMP dalam Menyelesaikan Soal Numerasi - Aditama, Fauziyah Kartika; Wijayanti, Pradnyo (Universitas Negeri Surabaya, 2025)
Critical thinking skills are important for students to have in solving simple and complex problems. This research is a qualitative study which aims to describe junior high school students critical thinking skills in solving numeracy problems. The subjects of this research were three students in VIII class of junior high school. Data collection techniques used numeracy tests and interviews. The results of this research are (1) Students who show interpretation, analysis, and explanation can mention important information in the question narrative and diagrams presented, use various mathematical symbols, and explain the solution steps coherently; (2) Students who show interpretation, analysis, evaluation, explanation, and self-regulation can mention important information in the question narrative and diagrams presented, use various numbers and mathematical symbols, show other ways to solve the problem, explain the solution steps coherently, and check again the steps taken in solving the numeracy problems; (3) Students who show interpretation, analysis, evaluation, inference, explanation, and self-regulation can mention important information in the question narrative and diagrams presented, use various numbers and mathematical symbols, show other ways to solve problems, analyze data and results calculations that have been carried out to make the right conclusions, explain the solution steps again in a coherent manner, and double check the steps taken in solving the problem. From this research, students need to be accustomed to understanding mathematical concepts by using questions in the context of everyday life such as numeracy problems.